Posture variation among office workers when using different information and communication technologies at work and away from work - Ciccarelli, Marina; Straker, Leon; Mathiassen, Svend; Pollock, Clare (Taylor & Francis Ltd., 2014)
Office workers perform tasks using different information and communication technologies (ICT) involving various postures. Adequate variation in postures and muscle activity is generally believed to protect against musculoskeletal complaints, but insufficient information exists regarding the effect on postural variation of using different ICT. Thus, this study among office workers aimed to determine and compare postures and postural variation associated with using distinct types of ICT. Upper arm, head and trunk postures of 24 office workers were measured with the Physiometer R over a whole day in their natural work and away-from-work environments. Postural variation was quantified using two indices: APDF(90-10) and EVA(sd). Various ICT had different postural means and variation. Paper-based tasks had more non-neutral, yet also more variable postures. Electronics-based tasks had more neutral postures, with less postural variability. Tasks simultaneously using paper- and electronics-based ICT had least neutral and least variable postures. Tasks without ICT usually had the most posture variability. Interspersing tasks involving different ICT could increase overall exposure variation among office workers and may thus contribute to musculoskeletal risk reduction.